Aesthetic Normativity in Kant’s Account: A Regulative Model - Feloj, Serena (Con-Textos Kantianos. International Journal of Philosophy, 2020)
The notion of normativity has been key to an actualizing reading of the subjective universality that for Kant characterizes the aesthetic judgment. However, in the scholarly literature little discussion is made, somehow unsurprisingly, of what exactly we should understand by normativity when it comes to Kant’s aesthetics. Recent trends show indeed the tendency to take normativity very broadly to the point of nuancing most of its core meaning. Based on how we speak about normativity in aesthetics, we seem indeed to have accepted that every kind of evaluative process is normative. I will argue that the sentimentalist elements of Kant's account call for a revision of its normative interpretations, for a better framing of its subjective universalism, and finally for a reconsideration of aesthetic normativity in favour of regulativity.